DOZ047.86: Open tracheostomy vs percutaneous tracheostomy in pediatrics. (24th June 2019) - Urquizo, M; Lobos, P; Coraglia, C; Mercado, P; Gallegos, D F
Abstract: Introduction: Tracheostomy is one of the most frequent surgical procedures in chronically ill pediatric patients and mechanical ventilatory assistance. The most widely used technique is open; however, the percutaneous technique guided by endoscopy is becoming increasingly common. Due to the current controversy, this study presents our experience in both techniques. Methodology: Retrospective and descriptive analysis was carried out of 100 patients selected between 2010 and 2017. They were divided into two groups: open tracheostomy (TA) and percutaneous tracheostomy (PT), with 50 patients each according to the technique used. The age, diagnosis, indication of tracheostomy, days of intubation, endoscopic findings, cannula size, surgical time, intraoperative complications, and definitive decannulation were analyzed. A bibliographic review was also carried out. Results and Discussion: The main indication for tracheostomy in both groups was prolonged orotracheal intubation (TA group 78% and TP group 82%). Children who underwent percutaneous tracheostomy were older in age (median age of 9 years for TA group and 2.5 years for PT group). There were no significant differences regarding the days of previous intubation: 19 days for the TA group and 13 days for the TP group. Weaning was achieved before mechanical ventilation for the TP group (7 days in the TP group and 19 days in the TA group). The surgical time was almost 50% less for the TP group (TA group 80 minutes and TP group 45 minutes). There were no intraoperative complications in any group. Distant complications were more frequent in the TA group (34%). Definitive decannulation was achieved in 17 patients in the TA group (34%) and in 19 patients in the TP group (38%). The long-term follow-up was performed for 8 months by the TA group ( r : 1–36 m) and 9 months by the TP group ( r : 1–48 m). Conclusions: Percutaneous tracheostomy is feasible in children. Simultaneous endoscopic vision is recommended for the control of complications during the procedure. At the same time it allows us to diagnose preexisting injuries. The size of the tracheostomy kit should be adjusted to the age of the patient and the size of the tracheostomy cannula to perform a safe tracheostomy.